The Prevalence of Unmet Need and Its Related Factors for Family Planning in Khuzestan Province, Iran: An Epidemiologic Study - Parvin Abedi; Malihe Botyar; Poorandokht Afshari; Farideh Namvar (Iran University of Medical Sciences, 2015)
Background: Women with unmet need are those who are sexually active in the reproductive age, but do not use any method of contraception despite they do not want more children. These women are at risk of unwanted pregnancies and abortions that can lead to maternal morbidity and mortality. The aim of this study was to evaluate the prevalence and related factors to unmet need for family planning among reproductive aged women in Khuzestan province, Iran, 2012-2013.  Methods: Samples were selected randomly from nine cities in the province. Data was collected using a questionnaire which was completed by interview. A 46 item questionnaire was designed to collect data about unmet need in family planning. Data were analysed using SPSS ver19. Descriptive statistics, Independent t-test, chi-square, and logistic regression tests were utilized for analyzing data.  Results: Unmet need was 80 (3.42) for limiting and 288 (9.59) for spacing, The prevalence of unmet need in Khuzestan Province was 13%. The unmet need group had more pregnancies and live children compared to the met need group (P<0.05). The women with her husband with primary education compared to illiterate ones, women with university education compared to illiterate ones, women with good knowledge about contraceptive methods compared to those with poor knowledge, were less likely to have unmet need.  Conclusion: The unmet need for family planning in the Khuzestan province is rather high compare to some statistics from other cities as well as in the whole country. Improving awareness about family planning can help women to decide about safer and more reliable contraceptive methods.